University students’ experience of online space while engaging in synchronous learning via videoconferencing amidst the pandemic - Lee, Ahram; Lee, Jee Young; Jung, Eunju (Frontiers in Psychology, 2023)
Background: The high infectivity and fatality of COVID-19 has changed the mode of higher education from onsite to online. Although many studies investigated the effectiveness and satisfaction of online education, little is known regarding university students’ lived experience of online space during synchronous learning via videoconferencing. Objective: The present study explored how university students experienced online space when engaging in synchronous learning via videoconferencing platforms during the outbreak of the pandemic. Method: The phenomenological approach was chosen to primarily explore students’ experience of online space as well as their experience of embodiment and relations to self and others. Interviews were conducted with nine university students who voluntarily participated to share their experience of online space. Results: Three core themes were generated from the descriptions of experiences provided by the participants. For each core theme, two sub-themes were emerged and described. The analysis of the themes demonstrated that online space was experienced as being separate from home but also inseparable because it was an extension of the comforts of home. This inseparableness is also reflected in the virtual classroom where the rectangular screen presented on the monitor is always shared with everyone in the class. Moreover, online space was perceived as having no transitional space in which spontaneity and new encounters occur. Finally, the presence of self and others was experienced differently in online space due to the participants’ choices of being seen or heard using their microphones and cameras. This led to a different sense of togetherness in online space. The insights gained from the study were discussed in relation to considerations for online learning in the post-pandemic era. Conclusion: Based on the emerged themes from the results, the current study concluded that the online space created by technologies cannot be a complete substitute for traditional face-to-face classrooms and suggested possible implications for designing and using online space in university education.